Rac mediates TNF-induced cytokine production via modulation of NF-kappaB. - Williams, L; Lali, F; Willetts, K; Balague, C; Godessart, N; Brennan, F; Feldmann, M; Foxwell, B (2008)
TNF is a key factor in a variety of inflammatory diseases. Here we report that TNF induced pro-inflammatory cytokine synthesis of IL-6 and IL-8 is mediated by the Rho GTPase Rac. TNF induces p42/p44, p54 and p38 MAPK kinase; these kinases have been implicated in control of cytokine synthesis. However, over-expression of a dominant negative form of Rac strongly inhibited TNF-induced p42/44 MAPK kinase activation, but had little effect upon JNK and no effect upon p38 MAPK activity. Another key signalling pathway controlling cytokine expression is NF-kappaB. When analyzing TNF-induced NF-kappaB activity via luciferase-reporter assays or via EMSA, we were able to show that the dominant negative version of Rac could completely abrogate TNF-induced NF-kappaB activity. In addition, we also observed that inhibition of the ERK pathway led to a reduction in TNF-induced NF-kappaB transcriptional activity; this was accompanied by an ablation of TNF-induced p65 phosphorylation at serine 276. This would suggest that TNF-induced activation of Rac, lies upstream of NF-kappaB activation, and that the inhibition of this pathway results in inhibition of cytokine production.